Cellular responses to a prolonged delay in mitosis are determined by a DNA damage response controlled by Bcl-2 family proteins. Issue 3 (March 2015) - Colin, Didier J.; Hain, Karolina O.; Allan, Lindsey A.; Clarke, Paul R.
Abstract : Anti-cancer drugs that disrupt mitosis inhibit cell proliferation and induce apoptosis, although the mechanisms of these responses are poorly understood. Here, we characterize a mitotic stress response that determines cell fate in response to microtubule poisons. We show that mitotic arrest induced by these drugs produces a temporally controlled DNA damage response (DDR) characterized by the caspase-dependent formation of γH2AX foci in non-apoptotic cells. Following exit from a delayed mitosis, this initial response results in activation of DDR protein kinases, phosphorylation of the tumour suppressor p53 and a delay in subsequent cell cycle progression. We show that this response is controlled by Mcl-1, a regulator of caspase activation that becomes degraded during mitotic arrest. Chemical inhibition of Mcl-1 and the related proteins Bcl-2 and Bcl-xL by a BH3 mimetic enhances the mitotic DDR, promotes p53 activation and inhibits subsequent cell cycle progression. We also show that inhibitors of DDR protein kinases as well as BH3 mimetics promote apoptosis synergistically with taxol (paclitaxel) in a variety of cancer cell lines. Our work demonstrates the role of mitotic DNA damage responses in determining cell fate in response to microtubule poisons and BH3 mimetics, providing a rationale for anti-cancer combination chemotherapies.